(untitled) (Malaysian Management Journal, 2006)
The integration of an economy to the global market, even when it leads to a higher standard of living, usually results in economic uncertainties and insecurity, as well as eroding social values and traditions of the society. Some people may gain, while some others may lose out from it, which may cause distributive conflicts to emerge. The economic uncertainties and insecurity, as well as the distributive conflicts that arise from globalisation, could disrupt the economy from securing the benefits of globalisation, and consequently could pose an impediment to economic growth. Hence, some scholars has argued that globalisation also increases the demand for greater role of government to stabilise the economy in terms of providing adequate social protection, if the benefits from globalisation are to be realised. This paper attempts to examine the impact of globalisation on the welfare of the Malaysian society, particularly on unemployment and poverty, and discusses the issues and challenges with regards to the provision of social protection in Malaysia. The paper argues that Malaysia needs a new perspective on social protection, as the existing institutions are deemed inadequate in providing protection to the society in the globalised economy.